ANT 2016/17: AWI airborne ultra-wideband radar data over the Jutulstraumen Glacier, western Dronning Maud Land, East Antarctica (MABAJU 2 project), Version 2 - Humbert, Angelika; Binder, Tobias; Steinhage, Daniel; Franke, Steven; Helm, Veit (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWIs multi-channel ultra-wideband radar system (AWI UWB) during the Antarctic season of 2016/17. The profiles are located near the grounding line of the Jutulstraumen Glacier in western Dronning Maud Land, East Antarctica as well as over the Halvfarryggen ice rise. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.
Keywords: Antarctic Ice Sheet; AWI UWB; Dronning Maud Land; Grounding Line; ice stream; Jutulstraumen; mass balance; Polar 6; radio-echo sounding